Development of compact seeded terahertz free-electron laser amplifier system at Kyoto University - S. Suphakul (2018)
© 2015 IEEE. We are developing a compact seeded terahertz (THz) free-electron laser (FEL) amplifier at the Institute of Advanced Energy, Kyoto University. The system consists of a photocathode RF-gun, a focusing solenoid magnet, a magnetic bunch compressor, focusing quadrupoles, an undulator, a laser system for the RF-gun and a THz parametric generator for seeding. The seeded THz lasers are amplified by FEL interaction inside the undulator. The target radiation wavelength is 300 to 800 μm. As the first step of the development, we evaluate expected power of coherent synchrotron radiations (CSRs). As the result it is found that the bunch charge from 50 to 75 pC will be suitable operation condition.